Tinjauan Prosedur Penerimaan dan Pengeluaran Kas Pada Badan Layanan Umum Daerah Puskesmas Gang Aut - Apriliani, Apriliani; Munawar, Aang (Jurnal Aplikasi Bisnis Kesatuan, 2023)
Cash receipts must be deposited into the bank and must not be allowed to sit for a long time at the Puskesmas, because this can lead to misappropriation or misuse of cash. Cash disbursements must be authorized and must be in accordance with needs, if the amount of cash issued is large enough, cash disbursements must use a check. The aims of this study were (1) to find out the documents used in the cash receipts and disbursements procedures of the Regional Public Service Agency (BLUD). (2) know the parties involved in the procedure for receiving and disbursing cash from the Regional Public Service Agency (BLUD). (3) find out how the flow or flowchart is in the procedure for receiving and disbursing cash from the Regional Public Service Agency (BLUD). The results of this study indicate that the cash receipts and disbursements of the Regional Public Service Agency (BLUD) at the Gang Aut Health Center have been carried out according to the Standard Operating Procedures (SOP) set by the BLUD treasurer.Keywords: Cash Receipt and Disbursement Procedure, BLUD